Activity-based costing : why and why not? - Choo, Hean (2014)
This project starts by looking at the technicalities of a traditional cost allocation system and the Activity-Based Costing (ABC) allocation system. It points out why the traditional system could not meet the present needs of companies competing in a competitive environment. The project also looks at why proponents of ABC claim it to be able to aid in managers’ decision-making process. On the other hand, criticisms of ABC made by various academicians were also reviewed. A case study was conducted on a company which, after an initial feasibility study, decided not to continue with further study on whether to implement ABC in its organization. The project looks at their reasons and comes to a conclusion that, for the company, the technical aspect of implementing ABC was not a major hindrance, rather it was the managers’ perception of the usefulness of ABC that was the major determinant. This indicates a discrepancy in the factors considered important by the academicians and the managers in the business environment in considering whether to implement or not implement ABC.